2011
DOI: 10.4021/cr85w
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Left Superior Vena Cava Draining into the Coronary Sinus: A Case Report

Abstract: Persistent left superior vena cava (PLSVC) is a congenital anomaly of the thoracic venous system resulting from the abnormal persistence of an embryological vessel that normally regresses during early fetal life. This anomaly is often discovered incidentally during surgery, cardiovascular imaging or invasive cardiovascular procedures. In most cases, a PLSVC drains into the right atrium through the coronary sinus. In the remainder of cases, it enters directly or through the pulmonary veins into the left atrium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Previous reports have suggested that up to 75% to 83% of unroofed coronary sinus cases are associated with PLSVC. 2,[7][8][9][10][11][12] A majority of PLSVC cases (80%-90%) involve the PLSVC draining to the right atrium through a dilated coronary sinus and are typically asymptomatic. 1,2,5 However, when the PLSVC communicates with the left atrium, either directly or via the unroofed coronary sinus or pulmonary vein, a right-to-left shunt results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have suggested that up to 75% to 83% of unroofed coronary sinus cases are associated with PLSVC. 2,[7][8][9][10][11][12] A majority of PLSVC cases (80%-90%) involve the PLSVC draining to the right atrium through a dilated coronary sinus and are typically asymptomatic. 1,2,5 However, when the PLSVC communicates with the left atrium, either directly or via the unroofed coronary sinus or pulmonary vein, a right-to-left shunt results.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][7][8][9][10][11][12][13] According to our literature review, all documented cases of stroke and thromboembolism in PLSVC have been attributed to right-to-left shunting, and the most common mechanism is through an unroofed coronary sinus into the left atrium. 5,8,[10][11][12] It is believed that stroke in the setting of PLSVC with left atrial drainage is likely caused by thromboembolism due to formation of thrombus occurring in the left superior vena cava or the left upper extremity veins and then subsequent paradoxical embolization via the right-to-left shunt. 4,[13][14][15] The diagnosis of PLSVC using TTE has been shown to depend on the correct administration of agitated saline into the left upper extremity peripheral vein.…”
Section: Discussionmentioning
confidence: 99%
“…Cases have been described where central venous catheters placed through the left internal jugular vein for vasopressor support were unintentionally placed into the tract continuous with the coronary sinus [ 5 , 6 ]. Particularly when the left subclavian vein is used for access, as a result of the abnormal proximity to the coronary sinus, there is additional concern for the catheter and associated guidewire causing arrhythmias, hemodynamic stability, and perforation of the heart [ 7 , 8 ]. Some authors have used catheters that were placed in the coronary sinus for drug and volume administration, although close proximity of the tip of the catheter to the coronary sinus could have the same risks as the guidewire [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, ultrasound echocardiography at bedside is preferred, in regards to some of its beneficial aspects. Echocardiography is preferred over other methods because there is no need for a nephrotoxic contrast agent, no radiation exposure, no risk of transport, its cost-effectiveness, and availability at bed-side [ 12 , 13 ]. An indication for the diagnosis of PLSVC during transthoracic echocardiography is a dilated coronary sinus.…”
Section: Discussionmentioning
confidence: 99%